Pemodelan Indeks Ketahanan Pangan di Indonesia Berdasarkan Pendekatan Regresi Logistik Ordinal Data Panel Efek Acak - Anisa Laila Azhar; Suliyanto Suliyanto; Nur Chamidah; Elly Ana; Dita Amelia (Universitas Gadjah Mada, 2023)
ABSTRACTIndonesia is an agricultural country with the agricultural sector being an important sector in supporting food needs. Food availability that is less than necessary can lead to an unstable economy, as well as disrupt national food security. This study was conducted to model The Food Security Index (Indeks Ketahanan Pangan, IKP) and to find out what factors affect the status of food security in Indonesia.The analysis method used in this study is the logistic regression analysis of panel data with random effects. The data used in this study is secondary data related to IKP sourced from the Ministry of Agriculture and factors that are suspected to affect IKP in each province sourced from the Central Statistics Agency (Badan Pusat Statistik, BPS) from 2019 to 2021. The results of the analysis showed that statistically, the variable percentage of stunted toddlers and the variable percentage of households with access to electricity had a significant effect on the IKP. In addition, the results of the model conformity test showed that the random effect panel data logistic regression model was more in line with the classification accuracy of 50.98% when compared to the standard logistic regression with a classification accuracy of 40.80%.